The Dialogical Theory of M.M. Bakhtin as a Form of Interaction of Cultures - Zakaryan, Hripsime (Bulletin of Yerevan University E: Philosophy, Psychology, 2023)
Recently, the problem of dialogue has been widely considered by philosophers, literary critics, linguists, culturologists, art historians and representatives of other scientific areas of the history of social thought. A special influence on the development of Western literary criticism and philosophical thought since the late 1960s. provided by the theory of dialogism of the Russian philosopher, art theorist, culturologist M. Bakhtin. In Bakhtin’s ideas, dialogue is the basis of existence: to be means to communicate dialogically. According to M. Bakhtin, the creator is constantly in dialogue with traditional and innovative works of art in search of new forms. The starting point of his judgments are the special dialogical relations of Dostoevsky’s heroes. Dostoevsky, in Bakhtinian definitions, with his wealth of polyphonic characters, formed an innovative device in world literature - the beginning of the "polyphonic novel". Analyzing the features of dialogues in Dostoevsky’s novels, depicting the method of creating a person in the space of dialogue, he shows the impossibility of a person’s existence outside of dialogue. The concept of "cultural dialogue", first used by M. Bakhtin, is understood as a close correlation of different cultural layers with the cultural past. Dialogical relations, in his opinion, can manifest themselves between different sign systems. Therefore, dialogue is also a cultural phenomenon. The article is devoted to the study of the process of formation of Bakhtin’s philosophical concepts, who considers dialogue as an ontological category. In Bakhtin’s concepts, dialogue is perceived as "communication" between "I" and "you" ("I" and "other"), that is, it is predominantly social in nature. The purpose of the article is to consider the features of the development and manifestation of the Bakhtinian theory of "dialogue", to show the ideological and theoretical prerequisites for dialogue, the development of ideas in Bakhtin’s epistemology as a methodological principle that is different from a monologue